Influence at Mass of the Base Isolation System in Affecting the Higher Modes of Vibration - et. al., Cici Jennifer Raj J, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Base Isolation is a technology of mitigating the effects due to earthquakes with the aspect of dissipating the seismic waves away from the superstructure, by isolating the superstructure from the ground.This concept is widely essential to be implemented in structures(buildings) irrespective of many factors. There are several materials which could be implemented as base isolator, however the need in reduction of the number of the isolators is essential dueto various factors which a developing country finds difficult to implement. In this paper, a three-storey unsymmetrical building to be considered for the study is isolated by varying the mass of the foundation beam, (Transfer beam) thereby reducing the number of isolators in the building.Furthermore,the mode shapes and frequencies of the structure without base isolation and with base isolation considering mass of the base isolation system as a key factor were analysed and compared and hence the variation in the mass of the isolation system has a promising effect in altering the higher modes of vibration. The analysis is prolonged using another methd using UBC-1997 provisions and compared. In both the methods, the influence of the mass of the isolation system has a remarkable effect in altering the higher modes of vibration.